Influence of cross‐sectional area and fat infiltration of paraspinal muscles on analgesic efficacy of epidural steroid injection in elderly patients. Issue 7 (30th June 2022) - Kim, Hee Jung; Rho, Miribi; Yoon, Kyung Bong; Jo, Minju; Lee, Dong Woo; Kim, Shin Hyung
Abstract: Background: An assessment of paraspinal muscle degeneration based on magnetic resonance imaging has been used to investigate both sarcopenia and myosteatosis. The morphologic changes in cross‐sectional area and fat infiltration of the paraspinal muscles can affect pain outcomes after epidural steroid injection. Methods: Patients ≥65 years of age who underwent fluoroscopy‐guided lumbar epidural steroid injections were enrolled. Good analgesia was defined as ≥50% reduction in pain score at 4 weeks after injection. Cross‐sectional area and grade of fat infiltration of the paraspinal muscles on magnetic resonance images at the level of L3–L4 disc were measured. Patient demographics, pain‐related factors, clinical factors, and paraspinal muscle measurements were compared between good and poor analgesia groups. The factors associated with pain outcomes after injection were identified using multivariate analysis. Results: A total of 245 patients consisting of 149 and 96 patients in the good and poor analgesia groups, respectively, fully satisfied the study criteria for analysis. Patients of older age, opioid use, and high‐grade foraminal stenosis were frequently observed in the poor analgesia group. The grade of fat infiltration of the paraspinal muscles was significantly higher in the poor analgesia group (Grade 2, 20.8% vs. 42.7%, p  < 0.001), and this result was predominantly observed in female patients. However, there was no difference in the muscle cross‐sectional area between the two groups (18.29 ± 3.16 vs. 18.59 ± 3.03 cm 2 /m 2, p  = 0.460). The percentage of patients with good analgesia decreased as the grade of fat infiltration increased (Grade 0 = 75.0%, Grade 1 = 65.8%, Grade 2 = 43.0%, p  < 0.001). Multivariate logistic regression analysis revealed that preinjection opioid use [adjusted odds ratio (aOR) = 1.926, 95% confidence interval (CI) = 1.084–3.422, p  = 0.025], moderate to severe foraminal stenosis (aOR = 2.859, 95% CI = 1.371–5.965, p  = 0.005), and high‐grade fat infiltration of the paraspinal muscles (aOR = 4.258, 95% CI = 1.805–10.043, p  = 0.001) were significantly associated with poor analgesia after injection. Conclusion: High fat infiltration of the paraspinal muscles at the mid‐lumbar region appeared to be an independent factor associated with poor analgesia after epidural steroid injection in elderly patients with symptomatic degenerative lumbar spinal disease receiving conservative care. However, the cross‐sectional area of the paraspinal muscles was not associated with pain relief after injection.